A study about clinic-epidemiological pattern of acute poisoning in pediatric age group - Ramawat, Pramila; Jain, Nilesh (Asian Journal of Medical Sciences, 2021)
Background: Poisoning is one of the most common causes for emergency hospitalization and mortality in children. Mostly it is accidental in nature and can be prevented by awareness in caregivers. Recently due to increased use of many new chemicals in homes and agriculture clinic etiological profile of poisoning is also changed. Aims and Objectives: To study clinic-epidemiological pattern of acute poisoning in hospitalized children and To evaluate association of clinicodemographic factors to age of intoxicated children to evaluate association of clinicodemographic factors to age of intoxicated children. Material and Methods: A cross sectional study was conducted from October 2019 to February 2020 in pediatric department of a tertiary care center. Child admitted with alleged history of poisoning included in study. Type and amount of poison, clinical presentation, outcome and demographic profile were recorded from medical records of patients. Results: Study was conducted among 50 patients of poisoning. 74% patients were under 5 year of age while 56% were boys and 44% were girls. Patients admitted due to ingestion of Insecticides and pesticides (18%), hydrocarbons (14%), medicines (12%) and agricultural products (8%), plant products ((16%) and others. Maximum number of patients intoxicated with household products (56%). Age was significantly associated with residence (p = 0.02) and place of exposure (p = 0.01) and nature of poisoning (p = 0.05). Conclusion: In children below 5 year of age incidences of poisoning are more frequent, most of the cases are accidental in nature and easily preventable. Proper care in this tender age is very important in order to prevent morbidity and mortality due to poisoning.